63 The "Brighton Connector": A Simple, Reproducible and Cost-Effective Technique for Bilateral Antegrade Cerebral Perfusion During Aortic Arch Surgery. (12th October 2021) - Holland, L; Singh, S; Vieira, M; Narayana, A; Lewis, M; Hyde, J; Modi, A
Abstract: Aim: Surgery of the aortic arch presents significant technical and physiological challenges. Selective antegrade cerebral perfusion (SACP) during arch surgery has been shown to improve mortality and neurological outcomes in these patients. At our centre, we aimed to develop a safe, reliable, and cost-effective technique to provide bilateral antegrade cerebral perfusion without the need of another pump head. Method: We developed our system using equipment that is included in the accessory packaging for the Sorin Xtra cell saver system, which is readily available in cardiac surgical units nationwide, but often discarded as it is not required. An EOPA arterial return cannula and the TRUE FLOW RDB SACP cannula were joined using our novel connection. Results: A single surgeon has used the "Brighton Connector" for 6 patients in the last two years. All patients made a satisfactory recovery with a 0% rate of mortality or permanent neurological deficit. Conclusions: All components in our circuit are already approved for use in cardiac theatres, and the connection tubing would normally be discarded, making our method cost neutral. We demonstrate through a case series that mortality and neurological outcomes are good and comparable with other techniques.